2009
DOI: 10.1111/j.1365-2184.2009.00583.x
|View full text |Cite
|
Sign up to set email alerts
|

Fibroblastic response to treatment with different preparations rich in growth factors

Abstract: Optimizing composition and use of platelet-rich products is crucial to enhancing the therapeutic potential of this technology. Our data show that the biological effects of PRGF may depend on concentration of platelets and on the anatomical source of the cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
162
0
3

Year Published

2011
2011
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 221 publications
(175 citation statements)
references
References 40 publications
10
162
0
3
Order By: Relevance
“…The positive effect of PRP on fibroblast proliferation has already been described by Anitua et al, 54 Creeper and Ivanovski, 55 and Passaretti et al 56 Unfortunately these teams did not use a polymeric scaffold, so it was not possible to observe the benefits from the multiplication of the positive effect on the fibroblasts from both the polymer scaffold and the PRP. Platelets were shown to release numerous GFs with mitogenic and anabolic function (eg, platelet-derived growth factor, epidermal growth factor, and transforming growth factor-beta).…”
Section: Absorbance (Au)mentioning
confidence: 91%
“…The positive effect of PRP on fibroblast proliferation has already been described by Anitua et al, 54 Creeper and Ivanovski, 55 and Passaretti et al 56 Unfortunately these teams did not use a polymeric scaffold, so it was not possible to observe the benefits from the multiplication of the positive effect on the fibroblasts from both the polymer scaffold and the PRP. Platelets were shown to release numerous GFs with mitogenic and anabolic function (eg, platelet-derived growth factor, epidermal growth factor, and transforming growth factor-beta).…”
Section: Absorbance (Au)mentioning
confidence: 91%
“…This was expected, as it had previously been demonstrated that PRGF, as well as growth factors secreted by macrophages, enhanced fibroblast, mesenchymal, and stromal stem cell proliferation. 2,[33][34][35][36][37] In general, ADSC proliferation in all preconditioned medium increased from day 1 to day 4; however, by day 7 it appeared that proliferation slowed, and in some cases cell number even decreased, potentially due to induced contact inhibition as the cells became confluent in the wells, or died off following exhaustion of medium nutrients. This may also have been because the conditioned medium used for the ADSCs was MSFM, which is unfavorable over the long-term for ADSC growth, or due to harmful factors expressed during macrophage apoptosis.…”
Section: Released Prgf Effect On Cell Proliferationmentioning
confidence: 99%
“…The latter could explain why an additional supplement with FCS is needed. In our hands, the combination of plasma and platelet proteins represents an excellent culture media for a wide range of cells including tenocytes [17], keratocytes and conjunctival fibroblasts [18], osteoblasts, and even stem cells. Such an approach will definitely avoid the use of products from animal origin and possible immunological concerns.…”
Section: Letter To the Editormentioning
confidence: 99%